The Cost of Warrants - Bierman, Harold (Journal of Financial and Quantitative Analysis, 1973)
It is likely that warrants will be used increasingly in the future by corporations both as means of sweetening other securities such as preferred stocks and bonds, and as securities in their own right. Many authors have analyzed the characteristics of warrants from the point of view of investors but attempts to develop a procedure for determining the cost to a corporation of issuing warrants have been lacking. We will find it convenient to measure the yield to a corporation of issuing warrants instead of common stock, rather than determining the percentage cost of warrants analogous to the cost of common stock equity, preferred stock, and interest-bearing debt.